2020
DOI: 10.3389/fimmu.2020.01874
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Fibrinogen Consumption and Profiles of Inflammatory Molecules in Human Envenomation's by Bothrops atrox in the Brazilian Amazon

Abstract: Snakebites are considered a major public health problem worldwide. In the Amazon region of Brazil, the snake Bothrops atrox ( B. atrox ) is responsible for 90% of the bites. These bites may cause local and systemic signs from acute inflammatory reaction and hemostatic changes, and present common hemorrhagic disorders. These alterations occur due the action of hemostatically active and immunogenic toxins which are capable of triggering a wide range of hemostatic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 76 publications
(89 reference statements)
2
12
0
1
Order By: Relevance
“…Thus, botrocetin exerted a feeble role in evoking thrombocytopenia during envenomation, and other proteins and mechanisms may be attributed to it. Moreover, the present findings (Fig 2 ) confirmed that SVMP had no involvement in venom-induced thrombocytopenia [7,57].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, botrocetin exerted a feeble role in evoking thrombocytopenia during envenomation, and other proteins and mechanisms may be attributed to it. Moreover, the present findings (Fig 2 ) confirmed that SVMP had no involvement in venom-induced thrombocytopenia [7,57].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 83%
“…At the laboratory level, patients present hemostatic alterations-e.g. consumption of blood coagulation factors, particularly of fibrinogen, factor V and VIII, thrombocytopenia, and increased levels of fibrinogen/fibrin degradation products-and inflammatory changes, as increased levels of C-reactive protein and interleukin 6 [4][5][6][7][8][9]. In vitro, BjV induces platelet aggregation in washed platelets, activates blood coagulation and promotes fibrin(ogen)olysis [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This, indeed, lends supports to the hypothesis that this trait is an ancestral relic and, assuming no ecological difference among the Bothrops species examined, not subjected to purifying selection pressure. However, as has been noted in clinical cases [ 24 , 52 ], human bite victims survive long enough for the additional depletion of fibrinogen to contribute to the consumptive coagulopathy; therefore, the documentation of the species with the greatest relative potency in this regard will contribute to the body of knowledge, which is useful for designing evidence-based clinical management strategies. The species with the most relatively potent action (small R and small A values) in this regard were the terrestrial species B. jararacussu (all tested), B. asper (Costa Rica and Ecuador only amongst those tested in this study), B. atrox (all tested), B. leucurus , B. moojeni (all tested) , B. neuwiedi (Curitiba, Brazil only amongst those tested in this study), B. pauloensis , and B. jararaca (all tested except Rio Negrino).…”
Section: Discussionmentioning
confidence: 99%
“…As this action is slower than the procoagulant toxicity, it has been proposed as being an evolutionary relic left over from the anticoagulant snakes from which Bothrops diverged prior to uniquely evolving procoagulant toxicity [ 36 , 43 ]. However, while the prey capture role is unresolved, the direct action upon fibrinogen is of relevance to human envenomations, as bite victims survive long enough for fibrinogen depletion to become a significant variable, and thereby contribute to consumptive coagulopathy [ 24 , 52 ]. Other activities of clinical significance have been documented in Bothrops venoms, including direct actions upon platelets, and vessel damage [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this study did not find a significant elevation of tumor necrosis factor alpha (TNF-alpha). Previous work has shown a relationship between increasing TNF and SBE ( 72 74 ). Our unanticipated finding may be due to the predominant species enrolled in this study, Agkistrodon contortrix , is known to typically have a less severe clinical course.…”
Section: Discussionmentioning
confidence: 91%